2013
DOI: 10.1016/j.apcata.2013.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A multiphase reaction medium including pressurized carbon dioxide and water for selective hydrogenation of benzonitrile with a Pd/Al2O3 catalyst

Abstract: The hydrogenation of benzonitrile was studied with a Pd/Al 2 O 3 catalyst in the presence of pressurized CO 2 and water. This multiphase reaction system was effective for the selective production of the desired primary amine of benzylamine with no deactivation of the catalyst. The enhanced selectivity to the primary amine resulted from its transfer into water phase, which prevented the primary amine from reacting with an intermediate of imine into the secondary amine in the organic phase (benzonitrile). In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…In our recent work, the effects of CO 2 and/or water have been investigated on selective hydrogenation of benzonitrile with Pd/Al 2 O 3 catalyst [15]. The selectivity to primary amine increased from 85% to more than 96% by the presence of CO 2 and water with no catalyst deactivation.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work, the effects of CO 2 and/or water have been investigated on selective hydrogenation of benzonitrile with Pd/Al 2 O 3 catalyst [15]. The selectivity to primary amine increased from 85% to more than 96% by the presence of CO 2 and water with no catalyst deactivation.…”
Section: Resultsmentioning
confidence: 99%
“…The carbamate salt is insoluble in BC organic phase, resulting in high selectivity to PEA. The formation of the carbamate salt from benzylamine and CO2 was reported by Chatterjee et al 15 and Yoshida et al 12 The formation of carbamate salt in hydrogenation of BN using NiCl2/NaBH4 in CO2 expanded ethanol at 303K was shown by Xie et al and they also observed an enhanced benzylamine selectivity.…”
Section: Possible Roles/functions Of Water and Co2mentioning
confidence: 72%
“…The temperature of the cell was controlled by a temperature controller and a heating jacket containing rod heaters. 12,19 The FTIR spectra were collected for a mixture of CO2 dissolved in liquid benzyl cyanide at different pressures.…”
Section: In Situ Ftir Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Relativelym ild conditions were achievedw ith Pd catalysts; however,t here is still much room for improvement with respect to both yield and selectivity. [12] Although, with the exception of gaseous reactions, [13] most previousm ethods with homogeneous and heterogeneous catalysts have been conducted in batch systems, continuous-flow systemsh ave several advantages over batch systemsi nt erms of environmental compatibility, efficiency,a nd safety. [14,15] High productivity and saving of energya nd space can be attained by using flow systems, and it is possible to adjust the quantity of production by controlling the rate of introductiono fs tarting materials ("just-in-time" production).…”
mentioning
confidence: 99%